Universal precautions provide appropriate protection during autopsies of patients with infectious diseases (2020)
The current COVID-19 pandemic has raised concerns about the safety of laboratory personnel who handle tissue samples that harbor pathogens, including performing autopsies. While pathologists have performed autopsies on infected patients for centuries, universal precaution protocols to limit exposure to pathogens were not developed until the 20th century. This paper reviews the history and effectiveness of universal precautions, with an emphasis on performing autopsies on COVID-19 patients.